La culture en allees dans la zone humide: Une association de l'elevage et de l'agriculture - Sumberg, J.E. (1984)
Review of work being carried out by ILCA's Humid Zone Programme based at Ibadan, Nigeria to improve small ruminant production in this area. Evaluates ways of linking crop & small ruminant production through the use of fast growing leguminous trees such as Leucaena leucocephala & Gliricidia sepium which can provide both high quality fodder & mineral rich mulch for crop production; with particular reference to the cut-and-carry feeding of browse to small ruminants & a partial budget analysis of short-term fallow grazing & continuous cropping.